Family care and reproductions health for teens: Applying 8 family functions during the transition growth - Theresia, Yoan Agnes; Sylvia, Ester Inung; Datak, Gad (GHMJ (Global Health Management Journal), 2022)
"As the spearhead of national development, sometimes teenagers are required to be perfect. What people don't even know is that sometimes we teenagers also have stories to tell. Share a laugh and be cheerful, that's what we are. In the end, life is not about being perfect but how we want to learn and grow together. It's okay, you are not alone, we are always there for you". Those are words I thought of when I saw teenagers. They grow rapidly, and I thought family plays important roles during the transition time from childhood to adulthood. This photo essay highlights eight (8) family functions in preventing teenagers facing problems during their transition growth, including early marriage, premarital sex, and drug abuse. Instead, by applying the cares and educations to the adolescents, the family can support and prepare their children to be more productive for better future. "Love your family, love your teenager, and love the future of your nation” .